Preferences and Willingness to Pay for Herpes Zoster Vaccination Among Chinese Adults: Discrete Choice Experiment - Yiqi Xia; Ming Wang; Mingzheng Hu; Yanshang Wang; Beibei Yuan; Dawei Zhu; Ping He (JMIR Publications, 2024)
BackgroundThe incidence of herpes zoster (HZ) is rapidly increasing, causing both clinical and economic burdens in China. Very little is known about Chinese residents' HZ vaccine preferences and willingness to pay (WTP) for each vaccination attribute. ObjectiveThis study aims to elicit the preferences of Chinese urban adults (aged 25 years or older) regarding HZ vaccination programs and to calculate WTP for each vaccination attribute. MethodsIn this study, we interviewed 2864 residents in 9 cities in China. A discrete choice experiment was conducted to investigate the residents' preferences for HZ vaccination and to predict the uptake rate for different vaccine scenarios. A mixed logit model was used to estimate the preferences and WTP for each attribute. Seven attributes with different levels were included in the experiment, and we divided the coefficients of other attributes by the coefficient of price to measure WTP. ResultsVaccine effectiveness, protection duration, risk of side effects, place of origin, and cost were proven to influence Chinese adults' preferences for HZ vaccination. The effectiveness of the HZ vaccine was the attribute that had the most predominant impact on residents' preferences, followed by protection duration. The residents were willing to pay CN ¥974 (US $145) to increase the vaccine effectiveness from 45% to 90%, and they would barely pay to exchange the vaccination schedule from 2 doses to 1 dose. It is suggested that the expected uptake could be promoted the most (by 20.84%) with an increase in the protection rate from 45% to 90%. ConclusionsChinese urban adults made trade-offs between vaccine effectiveness, protection duration, place of origin, side effects, and cost of HZ vaccination. Vaccine effectiveness was the most important characteristic. The residents have the highest WTP (CN ¥974; US $145) for enhancing the effectiveness of vaccines. To maximize HZ vaccine uptake, health authorities should promote vaccine effectiveness.